2017
DOI: 10.18632/oncotarget.19320
|View full text |Cite
|
Sign up to set email alerts
|

Tumacrophage: macrophages transformed into tumor stem-like cells by virulent genetic material from tumor cells

Abstract: Tumor-associated macrophages are regarded as tumor-enhancers as they have key roles in the subversion of adaptive immunity and in inflammatory circuits that promote tumor progression. Here, we show that cancer cells can subvert macrophages yielding cells that have gained pro-tumor functions. When macrophages isolated from mice or humans are co-cultured with dead cancer cell line cells, induced to undergo apoptosis to mimic chemotherapy, up-regulation of pro-tumor gene expression was identified. Phagocytosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 86 publications
(116 reference statements)
0
34
0
Order By: Relevance
“…If such cells originate in response to the attack from the immune system towards tumor cells, or as a strategy to increase the tumor cell viability and metastatic potential, is yet to be established. Literature data reported that murine peritoneal macrophages can phagocytize apoptotic BC tumor cells from cell lines in vitro, and acquire stem-like features in the following steps [77]. With reference to the xenograft milieu, another study reported the host macrophage invasion and the presence of multinuclear giant cells or foreign body giant cells at the implant site upon the injection of human mesenchymal stem cells with biopolymers in NOD scid mice, thus indicating that severely immunocompromised mice are able to retain a certain level of innate immune responsiveness [78].…”
Section: Discussionmentioning
confidence: 99%
“…If such cells originate in response to the attack from the immune system towards tumor cells, or as a strategy to increase the tumor cell viability and metastatic potential, is yet to be established. Literature data reported that murine peritoneal macrophages can phagocytize apoptotic BC tumor cells from cell lines in vitro, and acquire stem-like features in the following steps [77]. With reference to the xenograft milieu, another study reported the host macrophage invasion and the presence of multinuclear giant cells or foreign body giant cells at the implant site upon the injection of human mesenchymal stem cells with biopolymers in NOD scid mice, thus indicating that severely immunocompromised mice are able to retain a certain level of innate immune responsiveness [78].…”
Section: Discussionmentioning
confidence: 99%
“…However, the interaction might be much closer than previously expected. Zhang et al demonstrated that some circulating macrophages might be able to phagocyte apoptotic CTCs and incorporate the tumor DNA into their nuclei, consequently obtaining some malignant features like expression of epithelial markers (such as cytokeratins) and stem cell markers (e.g., OCT4) [78]. Consequently, circulating monocytes from solid cancer patients can express both CD163 and EpCAM.…”
Section: Interaction Of Ctcs With Macrophagesmentioning
confidence: 99%
“…Consequently, circulating monocytes from solid cancer patients can express both CD163 and EpCAM. This led to the concept of “tumacrophages,” which have the potential of invasive tumor cells but are protected against the immune system [78]. Even more, Gast et al showed in a seminal work that viable tumor cells can fuse with macrophages to create hybrid cells, sharing markers of both tumor cells and macrophages [79].…”
Section: Interaction Of Ctcs With Macrophagesmentioning
confidence: 99%
“…Mouse macrophages have a similar phenotype and express similar antigens as human macrophages [6]. They also resemble human macrophages functionally, e.g., regarding phagocytosis of tumor cells [7]. The most common murine cell lines for the study of macrophage function are RAW264.7 and J774 cells.…”
Section: Introductionmentioning
confidence: 99%